Impact of ACTH Signaling on Transcriptional Regulation of Steroidogenic Genes - Ruggiero, Carmen; Lalli, Enzo (Frontiers in Endocrinology, 2016)
The trophic peptide hormone adrenocorticotropin (ACTH) stimulates steroid hormone biosynthesis evoking both a rapid, acute response and a long-term, chronic response, via the activation of cAMP/protein kinase A (PKA) signalling. The acute response is initiated by the mobilization of cholesterol from lipid stores and its delivery to the inner mitochondrial membrane, a process that is mediated by the steroidogenic acute regulatory (StAR) protein. The chronic response results in the increased coordinated transcription of genes encoding steroidogenic enzymes. ACTH binding to its cognate receptor, melanocortin 2 receptor (MC2R), stimulates adenylyl cyclase, thus inducing cAMP production, PKA activation and phosphorylation of specific nuclear factors, which bind to target promoters and facilitate coactivator protein recruitment to direct steroidogenic gene transcription. This review provides a general view of the transcriptional control exerted by the ACTH/cAMP system on the expression of genes encoding for steroidogenic enzymes in the adrenal cortex. Special emphasis will be given to the transcription factors required to mediate ACTH-dependent transcription of steroidogenic genes.